Rekonstruksi Hukum Kewarisan dan Harta Bersama Berbasis Keadilan Gender - Mohammad Nur Salim; Isnatin Ulfah (Jurnal Ilmiah Penegakan Hukum, 2026)
Islamic family law in Indonesia faces challenges in adapting inheritance law and marital property distribution to contemporary social changes. Problems arise when wives become the primary breadwinners or bear dual domestic and public responsibilities, while existing legal provisions continue to apply formalistic distribution mechanisms. This study aims to analyze gender inequality in inheritance and marital property distribution and examine the relevance of substantive justice principles in resolving such disputes. This research employs normative legal research methods using statutory, conceptual, and gender analysis approaches. The legal materials consist of the Compilation of Islamic Law, court decisions, and relevant legal and gender literature. The findings indicate that several religious court decisions have adopted progressive approaches by granting a larger proportion of marital property to wives based on their economic and domestic contributions during marriage. This approach is consistent with the concepts of Qira’ah Mubadalah and Syirkah Abdan, which position husband and wife relations as proportional partnerships. This study concludes that the reconstruction of inheritance and marital property law is necessary to realize substantive justice that is responsive to changing gender roles in contemporary families.